The Process of Society Empowerment in Managing Waste for Sustainable Development (Study on Waste Bank in Sicanang District Belawan) - Mujahiddin, Mujahiddin (Italian Sociological Review, 2019)
The society-based waste management efforts can be part of efforts to support the sustainable development agenda or in other terms referred to as sustainable development. By empowering the society in waste management, it will indirectly reduce the volume of waste production to the landfill so that the accumulation of waste in the landfill that produces methane gas (CH4). This research was conducted by case study approach to the existing bank waste customers in SicanangBelawan district in Medan. The data that have been collected through interviews and subsequent observations are analyzed by qualitative approach interactive model as proposed by Miles and Huberman, which consists of three main things namely; data reduction, data presentation and conclusion or verification. The results of the study found that the community empowerment process in managing waste begins with the increase of public participation by changing the value of waste from unworthy into rupiah value through waste saving. Increased participation is then followed by dissemination of waste segregation and waste recycling training. The whole process has a positive effect on social, economic and environmental change. Where the three aspects of change is an integral part of the principles of sustainable development, namely; social development, economic development and environmental conservation.